Variable Findings for Drug-Induced Sleep Endoscopy in Obstructive Sleep Apnea with Propofol versus Dexmedetomidine. (April 2016) - Capasso, Robson; Rosa, Talita; Tsou, David Yung-An; Nekhendzy, Vladimir; Drover, David; Collins, Jeremy; Zaghi, Soroush; Camacho, Macario
Objective: To compare VOTE classification findings (velum, oropharyngeal-lateral walls, tongue base, and epiglottis) for drug-induced sleep endoscopy (DISE) among patients with obstructive sleep apnea (OSA) using 2 sedation protocols. Study Design: Case series with chart review. Setting: Single tertiary institution. Subjects: Patients with OSA who underwent DISE. Methods: A total of 216 patients underwent DISE between November 23, 2011, and May 1, 2015. DISE findings based on VOTE classification were compared between patients receiving the propofol- and dexmedetomidine-based sedation protocols. Results: Patients with OSA (N = 216; age, 44.3 ± 11.7 years; body mass index, 27.9 ± 4.8 kg/m 2 ) underwent DISE with intravenous administration of propofol (n = 52) or dexmedetomidine (n = 164). There were no statistically significant differences between the 2 groups in baseline apnea-hypopnea index, oxygen desaturation index, Mallampati score, tonsil size, Epworth Sleepiness Scale score, peripheral oxygen saturation nadir, age, sex, or body mass index. Patients in the propofol group had a significantly increased likelihood of demonstrating complete tongue base obstruction (75%, 39 of 52) versus partial or no obstruction (25%, 13 of 52) in the anterior-posterior dimension, as compared with the dexmedetomidine group (complete obstruction: 42.7%, 70 of 164; partial or no obstruction: 57.3%, 94 of 164; odds ratio: 4.0; 95% confidence interval: 2.0-8.1; P = .0001). Obstruction of other airway subsites was not significantly different. Conclusion: Use of propofol versus dexmedetomidine to induce sedation may have a significant effect on the pattern of upper airway obstruction observed during DISE. Randomized prospective studies are indicated to confirm these initial findings.